2006
DOI: 10.1590/s0102-695x2006000300004
|View full text |Cite
|
Sign up to set email alerts
|

The antibiotic activity of some Brazilian medicinal plants

Abstract: Chemical analysis revealed that the crude extracts contained tannins, steroids, phenols, fl avonoids, triterpenes and saponins: the activities were suffi ciently high to present the possibility of future identifi cation of the active components by bioassay-guided fractionation and purifi cation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
25

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(65 citation statements)
references
References 31 publications
3
36
0
25
Order By: Relevance
“…These substances have been shown to inhibit mainly Bacillus subtilis, Mycobacterium phei, Serratia marcescens, E. coli, Pseudomonas aeruginosa, Shigella and Streptococcus. According to GALLÃO et al 16, , moringa seeds consist of mostly proteins (approximately 40%), The lack of bactericidal effects in our ethanol-based soursop extracts matches findings published by LIMA et al 27 , who reported S. aureus, E. coli and Salmonella to be resistant to all soursop extracts based on 95% ethanol. On the other hand, bioactivity of water-based soursop extracts against S. aureus and V. cholerae may be related to the chemical structure of the active substances.…”
Section: Resultssupporting
confidence: 88%
“…These substances have been shown to inhibit mainly Bacillus subtilis, Mycobacterium phei, Serratia marcescens, E. coli, Pseudomonas aeruginosa, Shigella and Streptococcus. According to GALLÃO et al 16, , moringa seeds consist of mostly proteins (approximately 40%), The lack of bactericidal effects in our ethanol-based soursop extracts matches findings published by LIMA et al 27 , who reported S. aureus, E. coli and Salmonella to be resistant to all soursop extracts based on 95% ethanol. On the other hand, bioactivity of water-based soursop extracts against S. aureus and V. cholerae may be related to the chemical structure of the active substances.…”
Section: Resultssupporting
confidence: 88%
“…Arg. (batata-de-tiú) apresentou atividade antibacteriana (Lima et al, 2006) e moluscicida (Santos & Sant'Ana, 1999). Jatropha gossypiifolia reduziu significativamente a pressão sanguínea sistólica em ratos (Abreu et al, 2003).…”
Section: Em Nossa Senhora Do Livramento-mtunclassified
“…Como controle positivo utilizou-se ciprofloxacina (5µg) para bactérias gram-positivas (S. aureus e S. epidermidis) e amoxicilina (10µg) para bactérias gram-negativas (E. coli e P. aeruginosa) e como controle negativo 50µl de álcool 70°GL. Os resultados foram obtidos através da mensuração do diâmetro dos halos de inibição ao redor dos poços, com o auxílio de paquímetro e expressos em milímetros, de acordo a metodologia descrita por Lima et al (2006). A presença de zonas de inibição de crescimento de ≥9,0mm ao redor dos poços foi considerada como indicativo de atividade antibacteriana.…”
Section: Methodsunclassified